Independent or Bureaucratic? The Early Career Choice of an Architect at the Turn of the Twentieth Century in Germany, France and England - Andri Gerber (Footprint)
While the general historical perception of the architect conveys an image of him/her as an independent ‘genius-artist’ we should not forget how, in particular around the turn of the twentieth century, architects were primarily employed by communal, or state administrations. The need for architects in administrations was primarily a consequence of the rising independence of cities and the necessity to react to urbanization and property speculation, and later for the mass housing programs in the aftermath of the First World War.